Aggregation studied by laser diffraction in relation to plowing, soil organic matter, and lime in the Brazilian cerrados - Westerhof, R; Buurman, P; Griethuysen, C. van; Ayarza, Miguel Angel; Vilela, Lourival; Zech, W. (International Center for Tropical Agriculture, 1999)
In the Cerrados, a large savanna region in Brazil, the effects of different land use on aggregation in Oxisols were studied, using laser diffraction grain-size analyses. The topsoil of plowed systems had significantly fewer macroaggregates (194-2000 micro m) and a significantly larger fraction of microaggregates and primary particles (<76 micro m) than did pastures and native savanna. In plowed systems that were low in soil organic carbon (SOC), lime negatively affected aggregate stability. Lime addition had no effect on topsoil aggregation in land-use systems that were irregularly plowed and generally had a higher SOC content. For all the studied topsoils, pH KCl was positively correlated with the amount of clay dispersed after 3 h of shaking in water. Soil organic carbon did not influence clay dispersion in the range of soils studied. In continuous cropping systems in the Cerrados, a combination of mechanical stress, low SOC, and liming will increase the number of small aggregates and primary particles and hence contribute to destabilizing the soil structure.